Effects of different vegetation on soil microbial biomass carbon and nitrogen in newly cultivated land (Bangladesh Journal of Botany, 2021)
Effects of plant growth on the soil quality and microbial biomass carbon and nitrogen of newlyincreased farmland, providing a scientific basis for the improvement of the newly cultivated land quality and crop selection were studied. Results showed that planting Rosa chinensis Jacq (R), Ardisia crenata Sims (A), Salvia miltiorrhiza (L) and Solanum lycopersicum (S) had significant effects on soil nutrients in cultivated land. The average content of microbial biomass carbon and nitrogen in the rhizosphere soil of the four plants were 91.74 - 138.55 and 17.24 - 79.42 mg/kg, 164.05 - 184.00 and 28.43 - 62.31 mg/kg, 58.26 - 73.26 and 27.04 - 51.48 mg/kg,183.47 - 282.00 and 24.89 - 35.94 mg/kg, respectively. The soil microbial biomass carbon presents as S > A > R > L at the seedling stage, and S > R > L > A at the flowering stage. Similarly, soil microbial biomass nitrogen presents as R > A > S > L at seedling stage and L > A > S > A at flowering stage. Results fully indicate that the biomass carbon and nitrogen of plants with short growth cycles of newly cultivated land have a small change in the biomass carbon and nitrogen. During the growth process of different vegetation, the changes in rhizosphere soil microbial biomass, carbon-nitrogen ratio and microbial entropy were significantly different. The low shrubs showed an increasing trend, root-growing Salvia miltiorrhiza decreased, while Solanum lycopersicum with the shortest growth cycle showed first increasing and then decreasing trend.Bangladesh J. Bot. 50(3): 879-886, 2021 (September) Special